COMPREHENSIVE EVALUATION OF CANCER SCREENING PROGRAMS IN KAZAKHSTAN: BREAST, CERVICAL, AND COLORECTAL CANCER - Arman Khozhayev; Aruzhan Iniyat; Madina Issapova; Aida Baltabay; Bakdaulet Aitzhanov; Aigerim Iskakova; Barfinabonu Shonazarova; Yesseniya Laptiyeva; Bayansulu Aimurzina (Theoretical Hypotheses and Empirical Results, 2026)
In this scientific and analytical work, the indicators of incidence and mortality from cervical cancer, breast cancer and colorectal cancer in the regions of our country are considered. The screening methods currently used and the results of this preventive survey of the population are described in detail. Detailed step-by-step algorithms are presented, and the principles of organization and diagnostic capabilities of the screening program for the active detection of these nosological forms of malignant neoplasms in clinically asymptomatic individuals are reflected.